THE NEW GENERALIZED GRAVITATIONAL MODEL OF MIGRATION FOR GEORGIA (Globalization and Business, 2023)
Econophysics, or the theory of construction of models using physical assumptions in economics, already has a long history. For this purpose, the gravitational law of attraction was probably first used in the modeling of trade models between two subjects. The laws of gravitational and electrostatic attraction were then used to study migration between countries. The article adopts two new models (containing dummy variables) of migration from Georgia to leading European countries and USA using multivariate linear regression. They are based on the Lewer and van der Berg generalized gravitational model of migration between countries of The Organisation for Economic Co-operation and Development (OECD). Their model contains dummy parameters of border, the proximity of the state languages and colonial links in past. In this article we introduce a new dummy parameter "religion" of the model of migration from Georgia; It is hypothesized that migration between neighbor countries may not be analogous to the Newton's law of universal gravitation. In our view, it would be more appropriate to use other physical assumptions to construct such a migration model, for example a mathematical model of the law of equalization of temperatures in an area with different temperatures at different points.